2006
DOI: 10.1099/mic.0.28768-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the type III secretion system (TTSS) to virulence of Aeromonas salmonicida subsp. salmonicida

Abstract: The recently described type III secretion system (TTSS) of Aeromonas salmonicida subsp. salmonicida has been linked to virulence in salmonids. In this study, three TTSS effector genes, aexT, aopH or aopO, were inactivated by deletion, as was ascC, the gene encoding the outer-membrane pore of the secretion apparatus. Effects on virulence were assayed by live challenge of Atlantic salmon (Salmo salar). The DascC mutant strain was avirulent by both intraperitoneal (i.p.) injection and immersion, did not appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 36 publications
2
94
0
Order By: Relevance
“…Invasion of the epithelial layer by Gram-negative bacteria is often mediated by Type III secretion systems (T3SS). Aeromonas salmonicida has a functioning T3SS (Burr et al 2002(Burr et al , 2003 and we have shown it to be critical for virulence in Atlantic salmon (Dacanay et al 2006). The results of the present study suggest that the Fim pili allow A. salmonicida to come into close contact with the gut epithelium.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Invasion of the epithelial layer by Gram-negative bacteria is often mediated by Type III secretion systems (T3SS). Aeromonas salmonicida has a functioning T3SS (Burr et al 2002(Burr et al , 2003 and we have shown it to be critical for virulence in Atlantic salmon (Dacanay et al 2006). The results of the present study suggest that the Fim pili allow A. salmonicida to come into close contact with the gut epithelium.…”
supporting
confidence: 56%
“…The virulence of the mutant strain Δfim and its parental strain A449 were tested by intraperitoneal (i.p.) and immersion challenges conducted as per Dacanay et al (2006). Briefly, for the immersion challenge there were 2 tanks group -1 with ca.…”
Section: Methodsmentioning
confidence: 99%
“…Both intraperitoneal injection and immersion bacterial challenges of Atlantic salmon were conducted as described elsewhere (11). The parental, tapA::KO, and flp::Km strains were tested by immersion challenge in Saint John River Atlantic salmon.…”
Section: Vol 76 2008mentioning
confidence: 99%
“…salmonicida remains poorly understood, and no single characteristic or phenotype was found only in virulent strains (16,17,30,42) until the recent description of an A. salmonicida subsp. salmonicida type III secretion system (6,11).…”
mentioning
confidence: 99%
“…All these A. salmonicida subsp. salmonicida isolates were grown on furunculosis agar (H€ anninen & Hirvel€ aKoski, 1997) at 18 C for 24 to 72 h since it is at this temperature that this psychrophilic bacterium is usually most efficient at infecting fish (Beaz-Hidalgo & Figueras, 2012;Dacanay et al, 2006;Dautremepuits et al, 2006).…”
Section: Methodsmentioning
confidence: 99%